Pengembangan Aplikasi PraMetaVirLab (Praktikum Metabolisme Virtual Laboratorium) Berbasis STEM Sebagai Media Pembelajaran Biologi KelasXII SMA/MA: (Development of the STEM-based PraMetaVirLab (Virtual Laboratory Metabolism Practicum) Application as a Media For Biology Learning) - Amalia Rahma, Rina; Wardhani , Irma Yuniar (BIODIK, 2024)
This research uses R&D (Research and Development) research with a 4D development model adapted to 3D (Define, Design, Develop). The objectives of this research are: 1) To determine the procedure for developing the STEM-based PraMetaVirLab (Virtual Laboratory Metabolism Practicum) application as a Biology Learning Media, 2) To determine the level of feasibility of the STEM-based PraMetaVirlab (Virtual Laboratory Metabolism Practicum) application as a Learning Media in Class XII SMA/ M.A. The test subjects in this research were students in class XII MIPA MA Raudlatus Shibyan. Data collection techniques through questionnaires, interviews and documentation. The sampling technique used is saturated sampling which is a type of non-probability sampling. The validation results from material experts obtained an assessment with an overall average percentage of 92.5% including the "Very Valid" category and an assessment from media experts with an overall average percentage of 89.964% "Very Valid" category. In the feasibility assessment by teachers, a percentage of 80% was obtained with the "Practical" category used by teachers, while the overall percentage obtained by students was 83.3% with the "Very Practical" category used by students. Thus, the STEM-based PraMetaVirLab (Virtual Laboratory Metabolism Practicum) application as a Biology Learning Media for class XII SMA/MA is practically used by teachers and students. Abstrak. Penelitian ini menggunakan jenis penelitian R&D (Research and Development) dengan model pengembangan 4D yang diadaptasi menjadi 3D (Define, Design, Develop). Tujuan penelitian ini adalah : 1) Untuk mengetahui prosedur pengembangan aplikasi PraMetaVirLab (Praktikum Metabolisme Virtual Laboratorium) Berbasis STEM Sebagai Media Pembelajaran Biologi, 2) Untuk mengetahui tingkat kelayakan aplikasi PraMetaVirlab (Praktikum Metabolisme Virtual Laboratorium) Berbasis STEM Sebagai Media Pembelajaran Pada Kelas XII SMA/MA. Subjek uj coba dalam penelitian ini adalah peserta didik kelas XII MIPA MA Raudlatus Shibyan. Teknik pengambilan data melalui angket, wawancara dan dokumentasi. Teknik sampling yang digunakan ialah sampling jenuh yang termasuk jenis non probability sampling.. Hasil validasi ahli materi memperoleh penilaian dengan rata-rata presentase keseluruhan sebesar 92,5% termasuk kategori “Sangat Valid” dan penilaian dari ahli media dengan rata-rata presentase keseluruhan sebesar 89,964% kategori “Sangat Valid”. Pada penilaian kelayakan oleh guru didapat presentase sejumlah 80%  dengan kategori “Praktis” digunakan oleh guru sedangkan oleh peserta didik diperoleh rata-rata presentase keseluruhan sebesar 83,3%  dengan kategori “Sangat Praktis” digunakan oleh peserta didik. Dengan demikian, aplikasi PraMetaVirLab (Praktikum Metabolisme Virtual Laboratorium) Berbasis STEM Sebagai Media Pembelajaran Biologi kelas XII SMA/MA praktis digunakan oleh guru dan peserta didik.